Dukungan Infrastruktur Teknologi untuk Mempercepat Produksi dan Memperluas Pasar Kacang Teng-Teng di Kota Kupang - Liem, Ferdinan Nikson; Bria, Theresia Avila; Saduk, Melsiani Rosdiani Fillipin; Hattu, Edwin Pieter Dominggus; Wabang, Jhon Arnoldos (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Divan Karya peanut brittle (kacang teng-teng) business in Kupang City has experienced a decline in production capacity due to limited labor and the continued use of manual equipment. This community service program aims to improve productivity and market reach through the diffusion of production technology and digital marketing training. The solutions implemented include redesigning the roasting drum using heat-resistant aluminum with a bearing system, and developing a semi-automatic mixing device. Trial results show that roasting time was reduced from approximately 50 minutes to 10 minutes, increasing production capacity from 250 packages/day to 2,000 packages/day while reducing the required labor from two workers to only one. In terms of marketing, the business owner was successfully onboarded to digital platforms to expand product distribution. Overall, technology support significantly enhanced production efficiency and strengthened the competitiveness of this peanut brittle UMKM.